Improving Incident Command Assessment Tool: Too Complex to Be Informative? - Polikarpus, Stella; Kasepalu, Reet (Proceedings of the International ISCRAM Conference, 2026)
The Effective Command Behavioural Marker Framework (EC) is central to incident command training and assessment in Estonia, yet its implementation in practice, specifically how the assessment instrument is used by assessors, has not previously been examined using large-scale empirical data. This work-in-progress analyses 1,558 formal assessments across two command levels collected over nine years. We examine five-point and four-point scale utilisation across criteria and the implications of collapsing rarely used scale categories. Results show pronounced central-tendency scoring and limited use of extreme scale values, suggesting that parts of the current scale granularity and criterion set add little discriminative information in use. These findings indicate that assessment instrument complexity may constrain assessor judgement and reduce the transparency and formative value of feedback. We therefore propose an assessment approach that preserves the original conceptual structure while proposing clearer behavioural anchors and improved scoring defaults, to be validated prospectively in live assessments.